2020
DOI: 10.3390/nano10081547
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Assembly of Ultrathin NiO/MoS2 Electrodes for Electrocatalytic Hydrogen Evolution in Alkaline Electrolyte

Abstract: The development of non-noble metal catalysts for hydrogen revolution in alkaline media is highly desirable, but remains a great challenge. Herein, synergetic ultrathin NiO/MoS2 catalysts were prepared to improve the sluggish water dissociation step for HER in alkaline conditions. With traditional electrode assembly methods, MoS2:NiO-3:1 exhibited the best catalytic performance; an overpotential of 158 mV was required to achieve a current density of 10 mA/cm2. Further, a synergetic ultrathin NiO/MoS2/nickel foa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
3
1
Order By: Relevance
“…Similarly, the lowest point of the overpotential value at 10 mA/cm 2 reached 144 mV at current density i= 2.5 mA/cm 2 . In general, the sample at current density i =2.5 mA/cm 2 displayed the highest HER activity; moreover, the corresponding Tafel slope and overpotential value were smaller than the results of many previous public papers such as MO3-MoS2 hybrid nanospheres (200 mV and 74 mV/dec) [26], amorphous MoSx film (211 mV and 55 mV/dec) [19], N doped MoS2 (232 mV and 127 mV/dec) [30], NiS@MoS2 core-shell microspheres (208 mV and 62.4 mV/dec) [31], MoSx/V2O3 (145 mV and 45 mV/dec) [34] (it can be observed more information on table 3).…”
Section: E F Fect Of the Current Density On Her Activitycontrasting
confidence: 63%
“…Similarly, the lowest point of the overpotential value at 10 mA/cm 2 reached 144 mV at current density i= 2.5 mA/cm 2 . In general, the sample at current density i =2.5 mA/cm 2 displayed the highest HER activity; moreover, the corresponding Tafel slope and overpotential value were smaller than the results of many previous public papers such as MO3-MoS2 hybrid nanospheres (200 mV and 74 mV/dec) [26], amorphous MoSx film (211 mV and 55 mV/dec) [19], N doped MoS2 (232 mV and 127 mV/dec) [30], NiS@MoS2 core-shell microspheres (208 mV and 62.4 mV/dec) [31], MoSx/V2O3 (145 mV and 45 mV/dec) [34] (it can be observed more information on table 3).…”
Section: E F Fect Of the Current Density On Her Activitycontrasting
confidence: 63%
“…For the HER, the overpotentials of C, MoSe 2 @C and CMC-3 are 667 mV, 186 mV and 144 mV at the current density of 10 mA cm −2 , respectively (figure 3(a)). Even at higher current densities of 100 and 300 mA cm −2 , the CMC-3 features low overpotentials of only 245 mV and 268 mV, respectively, which are superior to those of Mo-based catalysts reported before [45][46][47][48]. Compared to C and MoSe 2 @C, it also shows a much smaller Tafel slope of 95.5 mV dec −1 , which suggests that the Volmer-Heyrovsky mechanism predominates the process of the HER catalyzed by the CMC (figure 3(b)) [49].…”
Section: Electrochemical Water Splitting Performancementioning
confidence: 67%
“…31,32 Doping or heterostructure engineering with suitable low-barrier water adsorption/dissociation components can be performed to activate the alkaline HER activity of MoS 2 . 22,30,33,34 Past studies have shown that the kinetic energy barrier for water dissociation is effectively reduced by the incorporation of Ni sites into MoS 2 (ΔG Hd 2 O = 0.66 eV for the Ni−MoS 2 system, 29 0.81 eV for the NiO−MoS 2 system, 35 and 0.05 eV for the Ni(OH) 2 /MoS 2 system 30 ). There are also reports that suggest that the combining of Ni-based catalysts with MoS 2 significantly improves the hydrogen adsorption/desorption process (at the Mo and S edge sites) with more near to zero ΔG H* values (−0.06 eV) for Ni−MoS 2 and Ni(OH) 2 /MoS 2 systems.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen adsorption free energy (Δ G H* ) values are reported to be −0.25 to −0.36 eV for the Mo and S edge sites of MoS 2 . , Despite the great HER activity in acidic solutions, MoS 2 nanosheets are HER inactive in alkaline medium due to unfavorable (high barrier) water dissociation on the surface. The kinetic energy barrier of the initial water dissociation step (Δ G H 2 O ) on MoS 2 is reported to be high up to 1.17 eV. , The unfavorable charge interactions and unsuitable orbital orientation are reported to be the major reasons for the unfavorable water adsorption and dissociation characteristics of MoS 2 . , Doping or heterostructure engineering with suitable low-barrier water adsorption/dissociation components can be performed to activate the alkaline HER activity of MoS 2 . ,,, Past studies have shown that the kinetic energy barrier for water dissociation is effectively reduced by the incorporation of Ni sites into MoS 2 (Δ G H 2 O = 0.66 eV for the Ni–MoS 2 system, 0.81 eV for the NiO–MoS 2 system, and 0.05 eV for the Ni­(OH) 2 /MoS 2 system). There are also reports that suggest that the combining of Ni-based catalysts with MoS 2 significantly improves the hydrogen adsorption/desorption process (at the Mo and S edge sites) with more near to zero Δ G H* values (−0.06 eV) for Ni–MoS 2 and Ni­(OH) 2 /MoS 2 systems. , Further, the introduction of plasmonic Au nanoparticles on MoS 2 nanosheets effectively increases the number of active hydrogen adsorption/desorption sites with more optimal (near-zero) Δ G H* values to improve the HER activity. Taken together, we have developed a plasmonic–excitonic Au–MoS 2 /NiO/Ni foam catalyst through a simple in situ strategy to achieve both the favorable hydrogen adsorption and low-barrier water dissociation sites for exhibiting highly active alkaline HER.…”
Section: Introductionmentioning
confidence: 99%